Buried‐heterostructure mid‐infrared quantum cascade lasers fabricated by non‐selective regrowth and chemical polishing. Issue 14 (1st July 2015) - Chang, C.‐C.; Kirch, J.D.; Buelow, P.; Boyle, C.; Kuech, T.F.; Lindberg, D.; Earles, T.; Botez, D.; Mawst, L.J.
Abstract : A novel fabrication method of buried‐heterostructure (BH) mid‐infrared quantum cascade lasers (QCLs) by using non‐selective regrowth of iron‐doped indium phosphide (InP) (Fe:InP), around deeply etched laser ridges, via metal‐organic chemical vapour deposition (MOCVD) and planarisation via chemical polishing is reported. Owing to better heat dissipation, the fabricated 4.75 μm emitting QCLs exhibit about three‐fold enhancement in maximum output power under continuous‐wave operation at room temperature ( T = 20°C) compared with that from lasers without the regrown InP. The demonstrated fabrication method provides a more flexible route to realising BH QCLs by removing strict requirements on the etched‐ridge sidewall profile, as well as on the physical dimensions of the dielectric mask for the regrowth via MOCVD. The method can be further employed for making large‐emitting aperture, closely packed arrays of QCLs, with planarised geometry, for coherent‐power scaling.